The musical experience : rethinking music teaching and learning - Barrett, Janet R.; Webster, Peter Richard, 1947- (New York : Oxford University Press, 2014)
This book proposes a new concept, musical experience, as the most effective framework for navigating the shifting terrain of educational policy as it is applied to music education. Other books that deal with music education reform often concentrate on non-musical topics at the expense of music listening, performance, and composition, or concentrate on only one of these at the expense of the others. This book works with musical experience as a comprehensive framework for all aspects of music education. This text defines musical experience as being characterized by the depth of affective and emotional responses that music engenders, and illustrate that its breadth is embodied in the infinite variety of meanings, both personal and communal, that music evokes. This book maps out the primary forms of musical engagement (performing, listening, improvising, composing, et cetera) as activities which play a key role in classroom teaching. This book also addresses the cultural dimensions of musical experience, which call for consideration of time, place, beliefs, and values placed upon musical activities, works, and genres. The book discusses how music teachers can most effectively rely on means of musical communication to lead students toward the development and refinement of musical skills, understandings, and expression in educational settings. This book expands upon the dimensions of musical experience and provides, from the forefront of the field, an integrated yet panoramic view of the educational processes involved in music teaching and learning.
New thinking for the study of music teaching and learning / Janet R. Barrett and Peter R. Webster, editors ; Section 1: Philosophy. Philosophical musings : reflections and directions / Betty Anne Younker ; Escaping versus confronting reality : politics and music education in the age of entertainment / Paul Woodford -- Section 2: Listening. Music listening vistas, visions, and vim / Jody L. Kerchner ; Life music as a beginning point : connecting with the intuitive listener / Rob E. Dunn ; Music listening spaces / Carlos Xavier Rodriguez -- Section 3: Cultural dimensions of music teaching and learning. Finding middle ground : music education in urban settings / Catherine Larsen ; Framing approaches to world music pedagogy in a local music culture / Valerie R. Peters ; Spaces for student voices : composition in schools and issues of social justice / Janice P. Smith -- Section 4: Creativity. Is a virtual composer in residence an oxymoron? / Bruce Carter ; Creative application : a way to include music composition and improvisation in the general music curriculum / Lois Veenhoven Guderian ; Fostering creativity in the performance ensemble / Kate Fitzpatrick -- Section 5: Evolving roles. Reframing leadership and the musical experience : the conductor as servant leader / Ramona M. Wis ; Reconsidering the performing ensemble class and the role of the conductor/teacher in music education / David S. Zerull -- Section 6: Reconceptualizing music teacher education. Preservice music teacher preparation for the conductor-educator role / Margaret H. Berg ; Music education : relevant and meaningful / David A. Williams ; "No actual teaching" : expanding preservice music teachers' imaginaries of teaching / Teryl L. Dobbs ; Building bridges to solve puzzles : strategic curriculum design in music teacher education / Michele Kaschub.
Includes bibliographical references and index.
Keywords: Music -- Instruction and study